2019
DOI: 10.1080/1533256x.2019.1637229
|View full text |Cite
|
Sign up to set email alerts
|

Insecure Attachment and Drug Misuse among Women

Abstract: The relationship between attachment and gender is well researched in social work, as is the influence of insecure attachment on drug misuse. However, discussion of the interrelationship among insecure attachment, gender, and drug misuse is sparse in the social work literature, with contradictory findings. The attachment literature indicates that males and females exposed to the same stressful events may differ in their reaction to stressors and to insecure attachments. Some studies find that gender differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…4 Thus, when the child does not receive the appropriate response from the caregiver, insecure binding styles are formed. 5 This idea was further developed by Mary Ainsworth, who found that the attachment style that develops is likely to be one of three types: secure, avoidant, or ambivalent. 6 A fourth category, the disorganized, was proposed afterwards by Main and Solomon.…”
Section: Mother and Stepfathermentioning
confidence: 99%
See 1 more Smart Citation
“…4 Thus, when the child does not receive the appropriate response from the caregiver, insecure binding styles are formed. 5 This idea was further developed by Mary Ainsworth, who found that the attachment style that develops is likely to be one of three types: secure, avoidant, or ambivalent. 6 A fourth category, the disorganized, was proposed afterwards by Main and Solomon.…”
Section: Mother and Stepfathermentioning
confidence: 99%
“…• Female gender has higher rates of comorbidity with major depressive disorder, anxiety disorders, eating disorders and post-traumatic stress disorder. 5 Throughout the story, Christiane struggles with issues related to self-image, as well as traumatic experiences and depressive and anxious feelings, even presenting suicidal ideation (Table III -Selfimage; The despair).…”
Section: Polydrug Usementioning
confidence: 99%